Nanotechnology-based approaches for antitubercular drug delivery - Darnis, Deny Susanti; Aminudin, Nurul Iman; Ismail, Mohamad Wafiuddin; Bakhtiar, M. Taher; Shafiee, Saiful 'Arifin; Danial, Wan Hazman; Hamzah, Nurasyikin (Elsevier, 2022)
Tuberculosis (TB) is an old disease that may have coexisted with humans for at least 15,000 years before the Neolithic [1]. TB is a communicable disease caused by Mycobac- terium tuberculosis and it remains the deadliest infectious disease killing 60 million people since 2000 [2,3]. The disease can be spread through the respiratory route, such as coughing from an infected person or gastrointestinal route possibly by drinking milk contaminated by bovine tubercle bacillus (M. bovis) by infecting the lung (pulmonary TB) and other sites (extrapulmonary TB) [1]. Almost a quarter of the world population is infected with TB [3] affecting more men than women. However, the treatment of TB has a fundamental issue that the long duration of the therapy which induce patient non-compliance, treatment failure and development of drug resistant by the pathogen [4]. Therefore, innovative strategy in the delivery of TB drugs such as in nanotechnology approach particularly in nanoparticle delivery would be more effective than conventional antibiotic treatment regimens via oral delivery. Nanoparticles which are administered via pulmonary inhalation gains special interest due to their intrinsic antimicrobial activity which acts directly to the lungs and avoiding first-pass metabolism reduction of dose and user-friendly administration (Fig. 10.1A) [5]. Nanoparticle is a small molecule sized less than 1000 nm that can encapsulate drugs and works efficiently in terms of improving physicochemical, stability and effectiveness of a drug. Nanoparticles can be made from different materials such as organic and polymer based nanocarriers (e.g polymer, solid lipid (SLNs), liquid crystal (LC), liposomes (LIP), micro- emulsions (MEs), carbon, and nanomicelles (NMs)) as well as inorganic nanocarriers (e.g gold, silver, and iron oxide) [6,7]. There are different methods available to produce nanopar- ticles resulting in different structures and sizes [5]. Some composition of different types of nanoparticles that have been tested for activity against Mycobacterium tuberculosis, such as those encapsulations first-or second-line anti-TB drugs, alone or in combination, as well as other potentially useful particles such as antimicrobial peptide and other therapeutic agents. Different properties of nanoparticles may influence their absorption, distribution, and efficacy in nanoparticle-based therapeutics as shown in Fig. 10.1B [5].